Role of the PsbI protein in photosystem II assembly and repair in the cyanobacterium Synechocystis sp. PCC 6803 - Dobáková, Marika; Tichy, Martin; Komenda, Josef (Plant physiology, 2007)
The involvement of the PsbI protein in the assembly and repair of the photosystem II (PSII) complex has been studied in the cyanobacterium Synechocystis sp. PCC 6803. Analysis of PSII complexes in the wild-type strain showed that the PsbI protein was present in dimeric and monomeric core complexes, core complexes lacking CP43, and in reaction center complexes containing D1, D2, and cytochrome b-559. In addition, immunoprecipitation experiments and the use of a histidine-tagged derivative of PsbI have revealed the presence in the thylakoid membrane of assembly complexes containing PsbI and either the precursor or mature forms of D1. Analysis of PSII assembly in the psbI deletion mutant and in strains lacking PsbI together with other PSII subunits showed that PsbI was not required for formation of PSII reaction center complexes or core complexes, although levels of unassembled D1 were reduced in its absence. However, loss of PsbI led to a dramatic destabilization of CP43 binding within monomeric and dimeric PSII core complexes. Despite the close structural relationship between D1 and PsbI in the PSII complex, PsbI turned over much slower than D1, whereas high light-induced turnover of D1 was accelerated in the absence of PsbI. Overall, our results suggest that PsbI is an early assembly partner for D1 and that it plays a functional role in stabilizing the binding of CP43 in the PSII holoenzyme.
Keywords: Bacterial Proteins; Photosystem II Protein Complex; Photosynthetic Reaction Center Complex Proteins; fotosyntetická reakční centra (proteinové komplexy); Synechocystis; fotosystém II (proteinový komplex); bakteriální proteiny